2009
DOI: 10.1016/j.bpc.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

An integrative simulation model linking major biochemical reactions of actin-polymerization to structural properties of actin filaments

Abstract: We report on an advanced universal Monte Carlo simulation model of actin polymerization processes offering a broad application panel. The model integrates major actin-related reactions, such as assembly of actin nuclei, association/dissociation of monomers to filament ends, ATP-hydrolysis via ADP-Pi formation and ADP-ATP exchange, filament branching, fragmentation and annealing or the effects of regulatory proteins. Importantly, these reactions are linked to information on the nucleotide state of actin subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 56 publications
0
24
0
1
Order By: Relevance
“…The polymerizationr eactiono fa ctin exhibits ah igh sensitivity for only some of the rate constants used to describe the polymerization process: k SNUC , k ASTB , k ASDB , k DIPB , k DIDB ,a nd k DITB . [35] These rate constantsdescribe the nucleation process and the association/dissociation processes of actin monomers at the barbed end of the filament, which exhibits faster elongation rates compared to the pointed end (see also Figure S1 in the Supporting Information, SI). [35] To quantify the effects of temperature, pressure, and co-solvents on the kinetics of the polymerization process, the rate constantsw ere varied to simulate the experimental datao btained.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The polymerizationr eactiono fa ctin exhibits ah igh sensitivity for only some of the rate constants used to describe the polymerization process: k SNUC , k ASTB , k ASDB , k DIPB , k DIDB ,a nd k DITB . [35] These rate constantsdescribe the nucleation process and the association/dissociation processes of actin monomers at the barbed end of the filament, which exhibits faster elongation rates compared to the pointed end (see also Figure S1 in the Supporting Information, SI). [35] To quantify the effects of temperature, pressure, and co-solvents on the kinetics of the polymerization process, the rate constantsw ere varied to simulate the experimental datao btained.…”
Section: Resultsmentioning
confidence: 98%
“…[35] These rate constantsdescribe the nucleation process and the association/dissociation processes of actin monomers at the barbed end of the filament, which exhibits faster elongation rates compared to the pointed end (see also Figure S1 in the Supporting Information, SI). [35] To quantify the effects of temperature, pressure, and co-solvents on the kinetics of the polymerization process, the rate constantsw ere varied to simulate the experimental datao btained. We found that in case of the Mg 2 + -induced polymerization reaction, the rate constant of the initial polymerization reaction observed, k obs ,i sm ainly effected by the nucleation step, in good agreement with literature data (examples are given in Figure 3).…”
Section: Resultsmentioning
confidence: 98%
“…Images were acquired from at least two separate experiments. Graphing analysis and curve fitting was performed using Graphpad Prism and FRAPAnalyser (Halavatyi et al, 2009). …”
Section: Frap Imagingmentioning
confidence: 99%
“…This stochastic approach provides precise information on the dynamics of G-and F-actin, including the structural compositions of actin filaments (Halavatyi et al 2009). We adapted the SSA for the simulation of a FRAP experiment, considering bleached and unbleached actin subunits as independent molecular species.…”
Section: Stochastic Simulation Algorithmmentioning
confidence: 99%